FRI0039 Synovial Macrophages Promote TGF-Beta Signaling but Protect against Influx of S100a8/s100a9-Producing Cells Following Intra-Articular Injections of Oxidized Low-Density Lipoproteins. (15th July 2016) - De Munter, W.; Geven, E.J.; Blom, A.B.; Walgreen, B.; Helsen, M.M.; Joosten, L.A.; Roth, J.; Vogl, T.; van de Loo, F.A.; Koenders, M.I.; van den Berg, W.B.; van der Kraan, P.M.; et al.
Abstract : Background: In previous studies we found that synovial macrophages regulate joint pathology during experimental osteoarthritis (OA) and, more recently, we found that high systemic levels of low-density lipoproteins (LDL) aggravate joint pathology during experimental OA with synovitis. LDL in inflamed synovium is oxidized and taken-up by macrophages, leading to an activated macrophage phenotype. Objectives: In this study, we investigate whether injection of oxidized LDL directly into a murine knee joint induces joint pathology and elucidate the role of synovial macrophages in that process. Methods: Synovium was obtained from end-stage OA patients and stained for apolipoprotein B (APOB). Murine knee joints were injected five consecutive days with oxLDL, LDL, or an equal volume of vehicle (PBS). This procedure was repeated in mice depleted of synovial macrophages by intra-articular injection of clodronate liposomes seven days prior to the consecutive injections. Joint pathology was investigated by immunohistochemistry and flow cytometry (FCM) analysis, and RNA expression and protein production by synovium were determined using RT-PCR and luminex, respectively. Aggrecanase activity was measured using NITEGE-staining and active TGF-β was measured using a functional CAGA-luciferase assay. Data are depicted as mean ± standard deviation. Results: Synovial macrophages and fibroblasts of end-stage OA patients showed extensive accumulation of APOB, the main protein present in LDL and oxLDL. Multiple injections of oxLDL in murine knee joints significantly increased TGF-β activity in synovial wash-outs by 28% [from 16562 ± 2326 relative light units (RLU) to 21151 ± 3823 RLU; P <0.05], but did not induce catabolic or inflammatory processes. In contrast, repeated injections of oxLDL in macrophage-depleted knee joints led to a 3.1 fold increase of synovial thickening, compared with injection of PBS ( P <0.01), while LDL injections did not alter synovial thickening. Protein and RNA levels of chemokines CCL2 and CCL3 were significantly upregulated in macrophage-depleted joints after oxLDL injections (6.7 fold and 4.6 fold, respectively; P <0.01). Furthermore, FCM-analysis revealed increased presence of monocytes (from 1422 ± 1105 to 3029 ± 1644 cells) and neutrophils (from 4014 ± 3511 to 12708 ± 7829 cells) in the synovium of macrophage-depleted joints after injection of oxLDL ( P <0.05), which was confirmed by immunohistochemical staining. Also protein levels of S100A8/A9, markers for inflammation, were significantly increased in synovial wash-outs of oxLDL-injected joints compared with LDL (fold increase 5.6; P <0.05) or PBS (fold increase 8.3; P <0.01) injection, as was NITEGE expression (fold increase 1.92; P <0.05). Interestingly, no raise in active TGF-β was measured in these macrophage-depleted joints. Conclusions: Synovial macrophages promote anabolic processes after intra-articular oxLDL injections. In absence of synovial macrophages, however, oxLDL induces production of pro-inflammatory mediators and aggrecanase activity, in combination with increased influx of monocytes and neutrophils. Disclosure of Interest: None declared